Soil test based optimal fertilizer requirements for attaining different yield targets of castor (Ricinus communis) in dryland Alfisols - AHMED, S RIAZUDDIN; KHADKE, K M; REDDY, K CHANDRASEKHAR; SANKAR, G R MARUTHI (The Indian Journal of Agricultural Sciences, 2014)
Soil-test crop response field experiments were conducted on castor (Ricinus communis L.) during kharif 1997 and 1998 under dryland conditions on Alfisols at Palem, Mahbubnagar district, Andhra Pradesh to optimise the fertilizer doses for castor. Soil test calibrations using multiple regression model were done for recommending fertilizer doses for targeted yield. Pooled soil test values of two years of experimentation were found to be ranging between 153 to 228 kg/hal of N, 6.3 to 108.0 kg/ha of P and 194 to 468 kg/ha of K. The organic carbon percentage in the soils range between 0.48 and 0.78. The castor seed yield in control was found to range between 341 and 1 104 kg/ha with a mean of 749.5 kg/ha. The castor seed yield in treated plots was found to range between 345 and 1 809 kg/ha with a mean of 988.5 kg/ha. It was found to be significantly correlated with both soil and fertilizer nutrients. Based on the study, the estimates of nutrient requirement (kg) for getting 100 kg yield of castor were found to be 2.825 for N, 0.94 for P and 2.895 for K. The soil and fertilizer nutrient efficiencies were found to be 12.35 and 24.1 for N , 14.75 and 11.2 for P and 8.3 and 9.0 for K respectively. The response yard stick (kg output/kg input) was found to be 3.485 based on the targeted yield coefficients. Using the fertilizer adjustment equations, a fertilizer ready reckoner has been developed for interpolating soil test based optimal fertilizer doses for attaining different castor yield targets of 0.8 and 1.0 tonne/ ha under dryland Alfisols at Palem in Andhra Pradesh.